2023
DOI: 10.3390/brainsci13020276
|View full text |Cite
|
Sign up to set email alerts
|

Switching from Rasagiline to Safinamide as an Add-On Therapy Regimen in Patients with Levodopa: A Literature Review

Abstract: Parkinson’s disease (PD) is a complex disease, and the treatment is focused on the patient’s clinical symptoms. Levodopa continues to be the most effective drug for symptomatic PD treatment. However, chronic levodopa treatment is associated with the development of motor complications in most patients. Add-on therapeutic drugs, such as dopamine agonists and monoamine oxidase B (MAO-B) inhibitors, for example, safinamide and rasagiline, may be a desirable addition to continuously increase the levodopa dose for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 55 publications
1
5
0
3
Order By: Relevance
“…Also, as some of the scales used assessed patients’ opinions, there could be a possible placebo effect. The main strength of the study is that it reinforces previous evidence of the benefit of switching from rasagiline to safinamide [ 18 , 39 , 42 ]. One recently published study was conducted with the aim of determining the levodopa equivalent dose.…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…Also, as some of the scales used assessed patients’ opinions, there could be a possible placebo effect. The main strength of the study is that it reinforces previous evidence of the benefit of switching from rasagiline to safinamide [ 18 , 39 , 42 ]. One recently published study was conducted with the aim of determining the levodopa equivalent dose.…”
Section: Discussionsupporting
confidence: 56%
“…As already noted in the aforementioned papers, this remarkable motor improvement could be attributed to safinamide’s non-dopaminergic mechanism of action. A recent review reported that switching from rasagiline to safinamide improved the wearing off phenomenon that occurs as the effect of the levodopa dose comes to an end until the clinical effect of the next one takes place, which could be useful to reduce the total daily dosage of levodopa, while improving the off and on times without troublesome dyskinesias and being more effective than other MAO-B inhibitors [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, the European Union (EU) and the US Food and Drug Administration (USFDA) approved safinamide, which is a reversible MAO-B inhibitor to combat mid- to late-stage PD. 19–21…”
Section: Introductionmentioning
confidence: 99%